Bioactive Activities of the Phenolic Extract from Sterile Bracts of Araucaria angustifolia - Thaís Estéfane Fischer; Amanda Marcondes; Danianni Marinho Zardo; Alessandro Nogueira; Ricardo C. Calhelha; Josiana A. Vaz; Lillian Barros; Acácio Antonio Ferreira Zielinski; Aline Alberti (MDPI AG, 2022)
Sterile bracts can represent 80% of Araucaria angustifolia pinecone and are a rich source of phenolic compounds. This study aimed to optimize the extraction of the phenolic compounds from Araucaria angustifolia bracts using response surface methodology; the bioactivity properties were also investigated. The effects of the ethanol concentration, solute/solvent ratio, and temperature in relation to the phenolic composition and antioxidant activity were evaluated. The quantification and identification of the individual phenolic compounds (using high-performance liquid chromatography) and their bioactivity were evaluated. The optimized extraction conditions, which detected gallic acid, catechin, epicatechin, quercetin, and kaempferol, were obtained using 60% ethanol at a ratio of 1:38 (w/v) and a temperature of 80 °C. The extract showed high levels of phenolic classes and antioxidant activity. The extract also showed an inhibitory activity for pathogenic (approximately 80%, 10,000 µg/mL) and lactic acid (27.9%, 15,000 µg/mL) bacteria strains. The α-glucosidase inhibitory activity was approximately ten times greater than acarbose, demonstrating its high antiglycemic potential. No antioxidant and anti-inflammatory cellular activity were determined; however, a high cytotoxicity for non-tumor cells and the antiproliferative activity against the tumor cells were observed. Overall, the phenolic extract showed promising action in relation to the fight against the diseases related to oxidative stress and, hopefully, the application of the safe concentrations of the extract, based on bioavailability assays, can be verified.